Konstruksi Konsep Dakwah dan Syarah Hadis Oral Habib Ja’far bin Husein dalam Akun YouTube Jeda Nulis - Arif Muhammad Hasibuan Arif (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2023)
Habib Ja'far's Hadith in the Jeda Nulis account. Starting from the initial assumption that, the purpose of creating the 'Jeda Nulis' account is to convey Habib Ja'far's ideas and thoughts visually based on the tendency of the millennial generation who prefer da'wah material in the form of comedy. Therefore, there are at least three questions raised This paper intends to examine the construction of the concept of da'wah and oral sharia in this article. 1)How is the construction of Habib Ja'far's da'wah concept based on the Hadith of the Prophet. 2)How are the religious tendencies and discourses in Habib Ja'far's oral Hadith sketches. 3)What are the implications for the concept of da'wah and diversity in the modern era. This type of research is literature using descriptive-qualitative methods with a critical paradigm. This research concludes that, one form of construction of Habib Ja'far's da'wah concept is to change the face of da'wah which tends to be rigid with comedic da'wah nuances based on the Prophet's hadith Ithaf al-shuruf fiqalb ikhwa. According to him, it is necessary to distinguish between propagating religion and diversifying jokes, what he does is use a touch of comedy with the aim of diversifying jokes. The implications of this da'wah concept lead to two aspects, namely positive and negative implications.